Evaluation of knowledge and clinical conduct in pharmaceutical professional practice (Research, Society and Development, 2021)
Community pharmacists have been expanding their scope of action. Dispensing has been added to the responsibilities in the Brazilian health system, such as the search for the development of clinical pharmaceutical services. Thus, the objective was to assess the knowledge of community pharmacists working on the clinical attributions established by Resolution No. 585/13, in the city of Teresina-Piauí. The work was carried out through two stages, in which 100 professionals were interviewed in each, all duly registered with the Regional Council of Pharmacy of Piauí (CRF-PI). The information was collected and analyzed using the Microsoft Office Excel® 2013 program. The results revealed that 82% claimed to know the aforementioned resolution, only 10% mentioned activities that did not fit the concept of pharmaceutical service. Regarding the pharmacotherapeutic follow-up, it was noticed that the vast majority were aware of the action (79%) and performed some type of clinical pharmaceutical service (82%). Only 6% said they did not have adequate space within the pharmacy/drugstore to carry out these services, 88% reported that they have already done/are doing specialization and only 3% declared that they were taking the pharmaceutical prescription. Although the vast majority of pharmaceutical professionals claim to be aware of resolution No. 585/2013, they do not know how to actually inform about this resolution. In addition, the low percentage of professionals who perform pharmaceutical prescriptions stands out. This context demonstrates that educational actions are needed to adequately prepare these professionals for clinical work.